A Case of Cushing's Syndrome due to Ectopic Adrenocorticotropic Hormone Secretion from Esthesioneuroblastoma with Long Term Follow-Up after Resection. (4th February 2018) - Matheny, Leslee N.; Sarkar, Sudipa; Shi, Hanyuan; Hu, Jiun-Ruey; Harmsen, Hannah; Abel, Ty W.; Jagasia, Shubhada M.; Bao, Shichun
Abstract : We present a case of a 52-year-old male who developed Cushing's Syndrome due to ectopic adrenocorticotrophic hormone (ACTH) secretion from a large esthesioneuroblastoma (ENB) of the nasal sinuses. The patient initially presented with polyuria, polydipsia, weakness, and confusion. Computed tomography scan of the head and magnetic resonance imaging showed a 7 cm skull base mass centered in the right cribriform plate without sella involvement. Work-up revealed ACTH-dependent hypercortisolemia, which did not suppress appropriately after high-dose dexamethasone. Subsequent imaging of the chest, abdomen, and pelvis did not reveal other possible ectopic sources of ACTH secretion besides the ENB. His hospital course was complicated by severe hypokalemia and hyperglycemia before successful surgical resection of the tumor, the biopsy of which showed ENB. Postoperatively, his ACTH level dropped below the limit of detection. In the ensuing 4 months, he underwent adjuvant chemoradiation with carboplatin and docetaxel with good response and resolution of hypokalemia and hyperglycemia, with no sign of recurrence as of 30 months postoperatively. His endogenous cortisol production is rising but has not completely recovered.